Implementasi Pendampingan Sertifikasi Halal Untuk Legalitas Pada UMKM Di Desa Bulurejo - Kartika, Cynthiagustin Cahya; Putri, Listia Aulia; Mu’arafah, Siti; Imamiy, Muhammad Izza; Wijanarko, Allyssa Fallahayati; Wulandari, Azizah Septiana; Wijayanti, Sella; Asari, Tiya; Nisa, Fajar Khoirun; Pramono, Muhammad Zuhud; Fahmi, Rijal Aulia; Sukma, Wachida Hanum; Tanfidiyah, Nur (Rahmah : Jurnal Pengabdian Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in national economic development, but MSMEs in Bulurejo Village do not yet understand business legality and the importance of halal certification. Both aspects play an important role in supporting the sustainability of MSME players in running their businesses. The objective of this Community Service (PKM) activity is to provide education and assistance regarding business legality and the importance of halal certification. The methods used in this Community Service (PKM) include counseling, mentoring, and direct assistance to MSME actors. The results of the Community Service (PKM) activity show that participants gained a better understanding of the importance of business legality and halal certification. Additionally, MSME operators were successfully assisted in obtaining their NIB and halal certification, which is beneficial for enhancing the competitiveness and credibility of their businesses.